Monitoring the Impact of Rapid Urbanization on Land Surface Temperature and Assessment of Surface Urban Heat Island Using Landsat in Megacity (Lahore) of Pakistan - Farid, Nasir; Moazzam, Muhammad Farhan Ul; Ahmad, Sajid Rashid; Coluzzi, Rosa; Lanfredi, Maria (Frontiers in Remote Sensing, 2022)
The present study focused on rapid urbanization due to the change in the existing landforms which has caused substantial adverse impacts on Urban Thermal Environment (UTE). In the present study we have acquired the Landsat data (TM and OLI) for the year of 1990, 2000, 2010 and 2020 to observe the land use changes (Vegetation Cover, Built Up Land, Barren Land and Water) in Lahore using supervised image classification method. Later the impact of urbanization has been examined with Land Surface Temperature (LST) and eventually the Surface Urban Heat Island (SUHI) has been calculated. Accuracy of the classified images revealed an overall accuracy (Kappa co-efficient) of 95.3% (0.929%), 92.05% (0.870%), 89.7% (0.891%), and 85.8% (0.915%) for the year of 1990, 2000, 2010, and 2020 respectively. It was found that vegetation cover decreased from 60.5% in 1990 to 47.7% in 2020 at the cost of urbanization. Overall built-up land increased by 23.52% from 1990-2020. Urbanization has influenced the LST and it was examined that maximum LST consistently increased with increase in built-up land. The difference between urban and rural buffer reveals that SUHI has also been increased over the years. SUHI has been raised from 1.72 oC in 1990 to 2.41 oC in 2020, total of 0.69 oC relative changed has been observed. It has also been observed that Normalized Difference Vegetation Index (NDVI) and LST has inverse relationship. The research outcomes of this study are useful for urban climatologist, urban planners, architects, and policymakers to devise a climate resilient policies, structure, and decisions to balance the urban green spaces for healthy urban environment.